DETERMINAN PERILAKU PENGGUNAAN MICROSOFT EXCEL DALAM MENYUSUN ANGGARAN - Husnunnida Maharani (Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to examine the factors that influence student behavior in budgeting using Microsoft Excel applications. This study develops model Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) by adding self efficiacy variable. The sample used in this study is the accounting students of the International University of Semen Indonesia 6th semester who took the subject of Budgeting as many as 48 respondents. The result of this study is the construct of the positive effect on the behavior of Microsoft Excel usage. Usability, credibility, attitudes, behavioral control, and self-confidence have a positive effect on the interest in using Microsoft Excel. Ease and subjective norms have a negative effect on the interest in using Microsoft Excel. The implication of this study is that the lecturer of the course subject to budgeting should pay more attention to usability, credibility, attitude, behavior control, and self efficacy of student to increase interest in using Microsoft Excel applications in budgeting.